Memlük Kahire'sinde Hanefi alimlerin hadis ilmine katkıları - Kepenek, Muhammed Yakup (My University, 2024)
Hanefîlerin hadis ilmiyle olan irtibatları hadis tarihinin önemli konularından biridir. Memlükler döneminde Hanefîlerin hadisle ilgili çalışmalarının ivme kazandığı görülmektedir. Memlük Kahire’sinde yaşamış olan Hanefîler yazdıkları hadis tahrîci, hadis şerhi, cerh-tadil, hadis usulü gibi eserlerle hadis ilmine katkıda bulunmuşlar, mezhebe ve mezhep büyüklerine hadis merkezli yöneltilen eleştirilere cevap vermişlerdir. Bu çalışmada Hanefîliğin Memlük Kahire’sinde yaygınlaşma sebepleri, Kahireli Hanefîlerin çevreyle münasebetleri, mansıpları, ilim mekânları, rihleleri, önde gelen aileleri ele alınmış, bazı kriterler belirlenerek hadisçi vasıfları üzerinde durulmuştur. Ayrıca Hanefî alimlerin hadis telif ve tedris faaliyetleri, hadis merkezli tartışmaları tespit edilmiş, hadis ilmiyle irtibatları farklı açılardan mukayese edilmiştir.

The relationship between Hanafi scholars and hadith science is one of the important subjects of hadith history. It is observed that the studies of Hanafis related to hadith gained momentum during the Mamluk period. The Hanafis who lived in Mamluk Cairo contributed to hadith science with their works such as hadith tahrir (compilation), hadith sharh (commentary), jarh-tadil (criticism of narrators), hadith usul (principles of hadith), and responded to the criticisms directed at the madhhab and its elders based on hadith. In this study, the reasons for the spread of Hanafiyyah in Mamluk Cairo, the relations of the Hanafis of Cairo with the environment, their positions, scientific institutions, travels, prominent families are taken into consideration, some criteria are determined and the characteristics of the hadith scholars are examined. In addition, the hadith compilation and teaching activities of Hanafi scholars, hadith-based discussions are determined, and their relationship with hadith science is compared from different perspectives.
Keywords: Cairo; Hadis; Hadis Mamluks; Hadith; Hanafi Sect; Hanafites fıgh; Hanefi fıkhı; Hanefî Mezhebi; Kahire; Memlükler